VARIABLE COSTING METHOD FOR COST PRODUCTION AT ABI CULINARY TRENGGALEK - Rohandayani, Ika Fitri; Andari, Atik Tri (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2023)
The purpose of this study is to analyze on production cost calculation by using variable costing method in 2022 period and to provide education related to accounting cycle record in Abi Culinary Trenggalek Small and Medium Enterprise. This study used applied study with quantitative method. The data collection techniques of this study were interview and documentation. The data which was used in the form of produced unit data and financial transaction data in 2022. The result of this study showed that production cost calculation by using variable costing method was more appropriate to be used because it entered the real cost that was occured in the production process in Abi Culinary Small and Medium Enterprise. Abi Culinary Small and Medium Enterprise still did simple financial record. Therefore, Abi Culinary Small and Medium Enterprise needed education on the accounting cycle to produce financial statements well.